DEVELOPMENT OF PROPHYLACTICS IN MATERNITY AND CHILD CARE IN THE REPUBLICS OF NORTHERN CAUCASUS IN THE FIRST HALF OF XX CENTURY - Z. I. Yakh"yaeva; Kh. M. Bataev ("Paediatrician" Publishers LLC, 2012)
We have reviewed a history of prophylactics development as a branch of maternity and child care in the republics of Northern Caucasus. We follow the development of this service from 1924; we make parallels between system of antenatal clinics development, that aimed at medical and sanitary literacy growth of the population, the development of system of regular medical check-ups of pregnant women in the country in general.